2013
DOI: 10.1111/bjh.12343
|View full text |Cite
|
Sign up to set email alerts
|

B‐cell lymphoma, unclassifiable, with features intermediate between diffuse large B‐cell lymphoma and burkitt lymphoma: study of 39 cases

Abstract: SummaryB-cell lymphoma, unclassifiable (B-UCL), with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma, is a poorly characterized entity. Therefore, we investigated cases of B-UCL treated by the Nebraska Lymphoma Study Group (NLSG). We searched the NLSG registry for years 1985-2010 for cases of B-UCL. Immunohistochemical stains and fluorescence in situ hybridization studies for MYC, BCL2 and BCL6 gene rearrangements were performed. Among the 39 cases studied, 54% were male and 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 31 publications
(61 reference statements)
4
62
0
Order By: Relevance
“…FISH testing is indicated in patients in whom BL is a consideration and in those who have a .20% incidence of MYC translocations, such as HGBL-NOS, plasmablastic lymphoma, and patients with histologic transformation from antecedent FL. 18 Immunohistochemistry can be useful for screening patients who require FISH because it is inexpensive, accessible, and routinely used in clinical laboratories. 19 The proliferation marker Ki-67 is always increased in BL but is more variable in HGBL-DH and is not a reliable marker for screening patients that require FISH.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…FISH testing is indicated in patients in whom BL is a consideration and in those who have a .20% incidence of MYC translocations, such as HGBL-NOS, plasmablastic lymphoma, and patients with histologic transformation from antecedent FL. 18 Immunohistochemistry can be useful for screening patients who require FISH because it is inexpensive, accessible, and routinely used in clinical laboratories. 19 The proliferation marker Ki-67 is always increased in BL but is more variable in HGBL-DH and is not a reliable marker for screening patients that require FISH.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…10,18 BCL2 is located on the chromosome arm 18q21 and was originally described in follicular lymphoma (FL). 30 BCL2 is a bona fide oncogene, 31 but lymphocytes overexpressing BCL2 require additional genomic alterations before developing overt lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Perry et al [17] reported 39 cases of BCLu-DLBCL/BL over a period of 15 years. In his study majority of patients presented with advanced-stage disease (62 %) with median overall survival (OS) of only 9 months and the 5-year OS was 30 %.…”
Section: Discussionmentioning
confidence: 99%
“…However, we continue to recommend CNS prophylaxis for patients with HGBL-NOS based on the increased risk observed in BCL-U and Burkitt lymphoma; in retrospective series, many patients with BCL-U morphology presented with IPI 3 to 5 even in the absence of MYC translocations. 53,54 However, this issue clearly warrants further study in larger datasets with central pathology review.…”
Section: Casementioning
confidence: 99%
“…However, we continue to recommend CNS prophylaxis for patients with HGBL-NOS based on the increased risk observed in BCL-U and Burkitt lymphoma; in retrospective series, many patients with BCL-U morphology presented with IPI 3 to 5 even in the absence of MYC translocations. 53,54 However, this issue clearly warrants further study in larger datasets with central pathology review.Outcome. We favor dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab (DA-EPOCH-R) for fit patients with HGBL-DH based on retrospective 26,52,55 and prospective data.…”
mentioning
confidence: 99%